Pericoronary adipose tissue attenuation predicts compositional plaque changes: a 12-month longitudinal study in individuals with type 2 diabetes without symptoms or known coronary artery disease - Katrine Schultz Overgaard; Thomas Rueskov Andersen; Laurits Juhl Heinsen; Gokulan Pararajasingam; Roda Abdulkadir Mohamed; Freja Sønder Madsen; Irmelin Irene Aagaard Biesenbach; Kurt Højlund; Jess Lambrechtsen; Søren Auscher; Kenneth Egstrup (Cardiovascular Diabetology)
Abstract Background Pericoronary adipose tissue attenuation (PCATa), derived from coronary computed tomography angiography (CCTA), is a novel marker of inflammation in the coronary arteries. Patients with type 2 diabetes mellitus (T2DM) are at elevated risk of coronary artery disease (CAD), potentially due to systemic inflammation. This study evaluated whether baseline PCATa predicts changes in plaque composition and burden over 12 months. Methods This prospective longitudinal study included 200 participants with T2DM, who had neither symptoms nor a prior diagnosis of CAD (mean age 61 ± 9.4 years, 72% male). PCATa was measured at the baseline scan along the proximal 40 mm of each major coronary artery, and the values were averaged to calculate the participant-level PCATa. High PCATa levels were determined using the validated cut-off of -70.1 Hounsfield units. Compositional plaque changes were quantified as the differences between baseline and 12-month scans, and plaque burden was calculated as the normalized atheroma volume. Multivariable regression analyses assessed the associations between baseline PCATa and compositional plaque changes and evaluated risk factors, including high PCATa, in predicting non-calcified plaque burden progression. Results Plaque compositional volumes and burden increased over 12 months, while PCATa remained stable. After multivariable adjustments, baseline PCATa was significantly associated with changes in total plaque volume (β = 0.005, p = 0.005), non-calcified plaque volume (β = 0.006, p = 0.007), total plaque burden (β = 1.7, p = 0.007), and non-calcified plaque burden (β = 2.0, p = 0.006), but not with calcified plaque volume or burden. High baseline PCATa was observed in 44 participants (22%) and was the only independent predictor of non-calcified plaque burden progression (odds ratio 3.5, p = 0.002). Conclusions Baseline PCATa is significantly associated with increases in total and non-calcified plaque volumes and burden over 12 months in participants with T2DM without symptoms or known CAD. High PCATa levels uniquely predict non-calcified plaque burden progression, suggesting that PCATa may serve as a marker for subclinical atherosclerosis progression. This warrants further investigation into PCATa for cardiovascular risk assessment, particularly in high-risk populations such as individuals with T2DM. Trial registration Trial registration: NCT06644651. Graphical abstract PCATa = Pericoronary Adipose Tissue attenuation. T2DM = Type 2 diabetes mellitus. CAD = Coronary Artery Disease. N = numbers. CCTA = Coronary CT angiography. Created in BioRender. Research insights What is currently known about this topic? 1. Type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD) share inflammatory mechanisms. 2. Individuals with T2DM face a two- to four-fold increased risk of CAD compared with those without T2DM. 3. Pericoronary adipose tissue attenuation (PCATa) is a novel marker of coronary inflammation. What is the key research question? Can baseline PCATa predict compositional plaque changes over 12 months in T2DM without known CAD? What is new? 1. Baseline PCATa relates to higher total and non-calcified plaque (NCP) volumes after adjustment. 2. Baseline PCATa associates with increased total- and NCP burden after multivariable adjustment. 3. High baseline PCATa (> -70.1 HU) independently predicts NCP burden progression. How might this study influence clinical practice? PCATa may be a marker for subclinical atherosclerosis progression.